2008
DOI: 10.1038/ijo.2008.131
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 status improves in overweight/obese women following a hypocaloric diet rich in breakfast cereals, and may help in maintaining fat-free mass

Abstract: Objective: To analyze the changes in vitamin B 6 status in women following slightly hypocaloric diets based on the relative increase consumption of foods whose intakes are below those recommended, and to study how these changes influence the proportion of fat-free mass. Design: Intervention study of two slightly hypocaloric diets: diet V (increased consumption of vegetables), or diet C (increased consumption of cereals, especially breakfast cereals). Subjects: A total of 49 women with a body mass index (BMI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…These data are consistent with our previously published study (Lewicka et al, 2012). Rodríguez-Rodríguez et al (2008) showed that vitamin B6 lessens the negative effect of hypocaloric diet and helps maintaining fat-free mass in overweight/obese women. A similar correlation was observed by Debski, Bertrandt, Klos, and Gralak (2007).…”
Section: Discussionsupporting
confidence: 94%
“…These data are consistent with our previously published study (Lewicka et al, 2012). Rodríguez-Rodríguez et al (2008) showed that vitamin B6 lessens the negative effect of hypocaloric diet and helps maintaining fat-free mass in overweight/obese women. A similar correlation was observed by Debski, Bertrandt, Klos, and Gralak (2007).…”
Section: Discussionsupporting
confidence: 94%
“…There are a several evidences that B 6 vitamin deficiency decreased body mass in rats [18,19]. In addition, B 6 supplementation improves status of overweight or obese woman [20]. Unfortunately, we didn't find in world literature articles dedicated to the effect of vitamin B 6 supplementation on gain weight.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have shown that vitamin B6 from oral supplements can be absorbed quickly, resulting in significant increases in plasma PLP (42). Many ready-to-eat cereals have been fortified with vitamin B6, and these have been shown to improve plasma PLP concentration (10, 43). …”
Section: Discussionmentioning
confidence: 99%